The 3D marine alienation title for marine cadastre in Kedah and Perlis / Nur Liyana Mat Rosdi - Mat Rosdi, Nur Liyana (2020)
The introduction of the marine cadastre in Malaysia is still in its infancy even up to date compared to other countries such as Australia, United States and Canada where the country has already been approaching with the introduction of marine cadastre in advance of us. However, Malaysia is still missing the references and sources of the marine cadastre applications. But, Malaysia is still not yet implemented the marine title documentation in Malaysia. The aim of this study to identify the best practice for 3D marine alienation title for marine by study case in Kedah and Perlis. The objective that come out parallel with the problem is to understanding a 3D marine alienation title for marine cadastre documentation, to create a 3D of marine in marine documentation for marine cadastre with buffer 3 nautical miles from low tide water and to propose a document of marine alienation for marine cadastre. The method that used in this research study is recreate sample of marine title documentation include with Qualified Title plan, generate 3 nautical miles shorelines in Map Info software and did data verification and testing by distributed the questionnaires and discussion among the agencies involved with marine cadastre. Finally, the end of result is produces a marine title documentation which distinguishes between a marine title and land title by attaching Qualified Title plan in two dimensions namely 3D and 2D by obtaining the approval of the marine cadastre specialist regarding the production of the grant sample.